PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 11 PADANG - Putri, Nadea Febridha (Departemen Matematika, 2024)
Grade VIII students at SMPN 11 Padang have low learning outcomes, which should be an indicator of students' understanding of the subject matter and one of the indicators of student success in mathematics. Comparing conventional methods with the Student Teams Achievement Division (STAD) cooperative model was the main driver for this study. The entire eighth grade at SMP Negeri 11 Padang participated in the study, which used a posttest-only control group design and quasi-experimental methodology. This tool served as the final evaluation. The results of the study led to the conclusion that H0 could not be accepted, as the P-value = 0.000, < α. As a result, the STAD model provided optimal results rather than the more traditional.Keywords– Conventional Learning, Learning Outcomes, Student Teams Achievement Division